Murder at the Blarney Bash - Hannah, Darci (Hannah, Darci. Beacon Bakeshop mystery., 2024)
While baking up a storm for the grand opening of the Irish import gift shop owned by her boyfriend's eccentric uncle, Finnigan O'Connor, Lindsey Bakewell needs the luck of the Irish when Finn is arrested for bludgeoning a man dressed as a leprechaun.